PENGEMBANGAN FLIPBOOK D’LAS LEMBAH ASRI BERBASIS MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MENULIS DESKRIPSI SISWA KELAS IV SD - Paramesti Nirwasita; Panca Dewi Purwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school students' descriptive writing skills still face various obstacles, particularly in organizing and expressing ideas in writing. Although cooperative learning models and digital media have been proven to support writing skills, the integration of local wisdom in digital teaching materials is still limited. This study aims to develop a D'las Lembah Asri digital flipbook based on local wisdom combined with the Cooperative Integrated Reading and Composition (CIRC) model, as well as to test its feasibility and effectiveness in improving the descriptive writing skills of fourth-grade students at SDN 3 Kutabawa. The study used the Research and Development (R&D) method with the ADDIE model. Expert validation results showed that the flipbook was in the highly feasible category with an average score of 91.67%. The effectiveness test showed an improvement in students' writing skills, marked by an average pre-test score of 62.05, a post-test score of 77.27, and an N-gain of 0.40 (moderate category). Thus, the D'las Lembah Asri flipbook based on the CIRC model is feasible and effective for use as a contextual learning medium in elementary schools.